Bentuk-bentuk interaksi sosial pada tokoh surya dan segara alam dalam Novel Noda Tak Kasat Mata karya Agnes Jessica dan Pulang karya Leila S. Chudori: Perspektif Georg Simmel - Kusuma, Monica Putri Perdana; Dewi, Novita (Aksara: Jurnal Bahasa dan Sastra, 2023)
The novel is one means of expressing a history and the existence of forms of interaction in each plot of the novel. This study aims to describe the forms of social interaction experienced by the main characters Surya and Segara Alam in the novels Noda Tak Kasat Mata by Agnes Jessica and Pulang by Leila S. Chudori. The approach used is Georg Simmel’s literary sociology theory approach. The research method used is descriptive qualitative research method. The data sources used are the novels Noda Tak Kasat Mata by Agnes Jessica and Pulang by Leila S. Chudori. The data used are excerpts from interactions between characters in the form of short dialogues. Data collection techniques used literature study and note-taking techniques for the two novels. The results of the study found that the forms of interaction experienced by the figures Surya and Segara Alam were exchange, conflict, domination, and sociability. In both novels, there is no prostitution as a form of social interaction.Keywords: social interaction, Georg Simmel, Noda Tak Kasat Mata, Pulang, novels